The Hippo Signaling Pathway in Cardiac Development and Diseases - Mia, Masum M.; Singh, Manvendra K. (Frontiers in Cell and Developmental Biology, 2019)
Heart disease continues to be the leading cause of morbidity and mortality worldwide. Cardiac malformation during development could lead to embryonic or postnatal death. However, matured heart tissue has a very limited regenerative capacity. Thus, loss of cardiomyocytes from injury or diseases in adults could lead to heart failure. The Hippo signaling pathway is a newly identified signaling cascade that modulates regenerative response by regulating cardiomyocyte proliferation in the embryonic heart, as well as in postnatal hearts after injury. In this review, we summarize recent findings highlighting the function and regulation of the Hippo signaling pathway in cardiac development and diseases.